MENGIDENTIFIKASI NILAI-NILAI ETIKA DAN MORALITAS DALAM CERITA BĀLA KĀNDA RAMĀYĀNA - I Dewa Gede Darma Permana (Pangkaja: Jurnal Agama Hindu, 2021)
Itihāsa is one part of the breadth of Vedic knowledge, which must be studied in the early stages of Vedic learning. Speaking further about Itihāsa, Itihāsa consists of two great epic literature, namely Ramāyāna and Mahābhārata. So that the initial knowledge that one can learn when studying Itihāsa is part of the orientation of the Ramāyāna book, namely Bāla Kānda. Reflecting on this, this research is interested in examining more deeply the story of the Bāla Kānda Ramāyāna, to find ethical and moral values contained therein in the perspective of Hinduism. In this study, several problems were also formulated, namely related to the nature of ethical values and morality, the story of Bāla Kānda Ramāyāna, and the ethical values and morality contained therein. By using research methods with the type of qualitative research, and literature study and using data analysis from Miles and Huberman. The results of this study indicate that the story of Bāla Kānda Ramāyāna contains many ethical and moral values that are useful for life. It is hoped that this research can be an initial provision for someone who is just learning the Vedas, then they can become a better person through the ethical values and morality they get.